Tuberculous Distal Biceps Tendon Rupture: Case Report and Review of the Literature - Boonrod, Artit (Case Rep Orthop, 2018)
Tuberculous distal biceps tendon rupture is a rare condition in orthopedics. Musculoskeletal tuberculosis usually presents with bursitis, synovitis, myositis, and osteomyelitis, conditions which demonstrate an excellent response to antituberculosis chemotherapy. Tendon rupture is often associated with delayed diagnosis and treatment. We report a rare manifestation of musculoskeletal tuberculosis in the distal biceps tendon with delayed diagnosis.